1999
DOI: 10.1007/s002130050942
|View full text |Cite
|
Sign up to set email alerts
|

L-701,324, a selective antagonist at the glycine site of the NMDA receptor, counteracts haloperidol-induced muscle rigidity in rats

Abstract: The present study suggests that L-701,324 exhibits a beneficial action in the animal model of parkinsonian rigidity, but not that of parkinsonian akinesia. Nonetheless, this compound is not devoid of motor side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…(Trevitt et al., 2009; Maj et al., 1990; Juszkiewicz et al., 1994; Juszkiewicz et al., 1995; Mandhane et al., 1997; Konieczny et al., 1999; Jagtap & Inamdar, 2001; Ossowska et al., 2001; Breysse et al., 2002; Moo‐Puc et al., 2003; Ossowska et al., 2003; Rukoyatkina et al., 2003; Wardas et al., 2003; Tanganelli et al., 2004; Ossowska et al., 2005; Zazpe et al., 2006; Lopez et al., 2007; Sibille et al., 2007; Ahemad et al., 2009; Beurrier et al., 2009; Góngora‐Alfaro et al., 2009; Konieczny et al., 2009; Ardashov et al., 2011; Joshi et al., 2011; Trevizol et al., 2011; Lopez et al., 2012; Shyamjith et al., 2012; Goudet et al., 2012; Acuña‐Lizama et al., 2013; Konieczny & Lenda, 2013; Atack et al., 2014; Ittiyavira & Ruby, 2014; Azam, et al., 2009; Zheng et al., 2014; Gmiro et al., 2015; Maurice et al., 2015; Nade et al., 2015; Bhangale & Acharya, 2016; Dhingra & Gahalain, 2016; Basu et al., 2017; Chitra et al., 2017; Gupta et al., 2017; Kumari et al., 2017; Kronbauer et al., 2017; Tian et al., 2017; Yang et al., 2016; Engelhardt et al., 2018; Slee et al., 2008; Saleem et al., 2019; Kabra et al., 2020; Łażewska et al., 2020; Chiu et al., 1981; Schmidt & Bubser, 1989; Schmidt et al., 1991; Kretschmer, 1994; Kretschmer et al.,…”
Section: Resultsmentioning
confidence: 99%
“…(Trevitt et al., 2009; Maj et al., 1990; Juszkiewicz et al., 1994; Juszkiewicz et al., 1995; Mandhane et al., 1997; Konieczny et al., 1999; Jagtap & Inamdar, 2001; Ossowska et al., 2001; Breysse et al., 2002; Moo‐Puc et al., 2003; Ossowska et al., 2003; Rukoyatkina et al., 2003; Wardas et al., 2003; Tanganelli et al., 2004; Ossowska et al., 2005; Zazpe et al., 2006; Lopez et al., 2007; Sibille et al., 2007; Ahemad et al., 2009; Beurrier et al., 2009; Góngora‐Alfaro et al., 2009; Konieczny et al., 2009; Ardashov et al., 2011; Joshi et al., 2011; Trevizol et al., 2011; Lopez et al., 2012; Shyamjith et al., 2012; Goudet et al., 2012; Acuña‐Lizama et al., 2013; Konieczny & Lenda, 2013; Atack et al., 2014; Ittiyavira & Ruby, 2014; Azam, et al., 2009; Zheng et al., 2014; Gmiro et al., 2015; Maurice et al., 2015; Nade et al., 2015; Bhangale & Acharya, 2016; Dhingra & Gahalain, 2016; Basu et al., 2017; Chitra et al., 2017; Gupta et al., 2017; Kumari et al., 2017; Kronbauer et al., 2017; Tian et al., 2017; Yang et al., 2016; Engelhardt et al., 2018; Slee et al., 2008; Saleem et al., 2019; Kabra et al., 2020; Łażewska et al., 2020; Chiu et al., 1981; Schmidt & Bubser, 1989; Schmidt et al., 1991; Kretschmer, 1994; Kretschmer et al.,…”
Section: Resultsmentioning
confidence: 99%
“…The antagonists of NMDA reporters include competitive antagonists (e.g., SDZ 220–581, MDL 100, 453), noncompetitive antagonists (e.g., MK-801, dextrorphan, PD 174494, CP-101, 606) as well as glycine site antagonists (e.g., MRZ 2/570, L-701,324, 7-chlorokynurenate, (R)-HA-966) [60]. Plenty of studies have demonstrated that NMDA receptor antagonists can attenuate catalepsy and counteract Parkinsonian rigidity induced by dopamine receptor antagonists in rats as well as akinesia and other motor complications in monoamine-depleted rodents [61,62,63,64]. Similar effects were also shown in an ifenprodil-treated MPTP-lesioned marmoset model [65].…”
Section: Key Targets Of Glutamate Receptors In Pd Treatmentmentioning
confidence: 99%
“…Several NMDA antagonists have been shown to reverse haloperidol-induced catalepsy and muscle rigidity (Mehta and Ticku, 1990; McAllister, 1996; Kaur et al, 1997; Konieczny et al, 1999) and also to reverse akinesia and other motor disturbances in reserpine-treated rodents (Carlsson and Carlsson, 1989; Kaur and Starr, 1995; Dutra et al, 2002). These effects have also been replicated in primate and rodent models of PD.…”
Section: Introductionmentioning
confidence: 99%